Anthropology of Ageing - Upadhyay, Vijay S. (Ranchi, India : V.S. Upadhyay, 1994)
Seminar papers.
Includes bibliographical references.
Keywords: Older people -- India -- Social conditions; Aging -- Cross-cultural studies